Censorship in Translation: The Dynamics of Non-, Partial and Full Translations in the Chinese Context - Tan, Zaixi (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2017)
This research focuses upon how the translation of certain types of literature in China evolved historically: from ‘non-translations’ (i.e., ‘translations’ unmade as well as made and yet strictly forbidden under given censorship conditions) to ‘partial’ or ‘full/near-full’ translations set against the backdrop of changing practices required by the country’s censorship policies. My analysis begins with an overview of the multi-faceted interface between censorship and translation, followed by the conceptualization of a typology of translations under censorship. This initial discussion, in turn, allows me to resituate specific translations, including the once absented translations of earlier times (i.e., prior to the 1949 Revolution or prior to the Cultural Revolution), which were initially taken at face value as ‘non-translations’ and yet which, later on, became ‘partial’ or ‘full/near-full’ translations under the country’s subsequently more relaxed censorial operations. I attempt to illustrate such shifts by means of in-depth discussion of the dynamic nature of translational commitment in connection with the change-resistant properties and evolving priorities of censorship. In illustrating my arguments, I will draw specific examples from case studies of three well-known censorship-affected translations – i.e., On China (Kissinger 2011), Lolita (Nabokov 1991) and The Good Earth (Buck 1960), which, I argue, epitomise the shifting degrees of translational commitment (‘non-,’ ‘partial’ and ‘full/near-full’) as they occurred in the Chinese context.